2007
DOI: 10.1007/s11240-006-9182-3
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast genome aberration in micropropagation-derived albino Bambusa edulis mutants, ab1 and ab2

Abstract: Two albino mutants (ab1 and ab2) have been derived from long-term shoot proliferation of Bambusa edulis. Based on transmission electronic microscopy data, the chloroplasts of these mutants were abnormal. To study the mutation of gene regulation in the aberrant chloroplasts, we designed 19 pairs of chloroplast-encoded gene primers for genomic and RT-PCR. Only putative NAD(P)H-quinone oxidoreductase chain 4L (ndhE; DQ908943) and ribosomal protein S7 (rps7; DQ908931) were conserved in both the mutant and wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 21 publications
5
29
0
1
Order By: Relevance
“…Kowata et al (1995) demonstrated that rice plantlets recovered from 1-month-old induced calluses were green while those obtained from 11-month-old calluses were 100% albino. Moreover, Artunduaga et al (1988) tested three common bermudagrass varieties and obtained 90% albino plants, while the characterization of two micropropagation-derived albino Bambusa edulis mutants demonstrated aberrations in their chloroplast genomes, causing reduction or absence of thylakoids, accumulating the lipids in plastoglobules (Liu et al 2007). B brizantha seems to be sensitive to long exposure to 2,4 D in culture, possibly responsible for the high frequency of albinism observed in this grass species in 4-month-old embryogenic callus culture.…”
Section: Repetitive Somatic Embryogenesismentioning
confidence: 99%
“…Kowata et al (1995) demonstrated that rice plantlets recovered from 1-month-old induced calluses were green while those obtained from 11-month-old calluses were 100% albino. Moreover, Artunduaga et al (1988) tested three common bermudagrass varieties and obtained 90% albino plants, while the characterization of two micropropagation-derived albino Bambusa edulis mutants demonstrated aberrations in their chloroplast genomes, causing reduction or absence of thylakoids, accumulating the lipids in plastoglobules (Liu et al 2007). B brizantha seems to be sensitive to long exposure to 2,4 D in culture, possibly responsible for the high frequency of albinism observed in this grass species in 4-month-old embryogenic callus culture.…”
Section: Repetitive Somatic Embryogenesismentioning
confidence: 99%
“…To do so, they employed a combination of suppressive subtractive hybridization (SSH) and microarray hybridization analyses, which mainly involved the stress response and photaesthesia. Subsequent research further showed that three chloroplast genes, NAD(P)H-quinone oxidoreductase chain 4, chloroplast 50S ribosomal protein L14, and ATP synthase beta chain, were supposed candidate genes for the albino mutants (Liu et al, 2007). However, current bamboo leaf color variation mechanisms were mainly derived from research on bamboo albino mutants from tissue culture lines.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this classification and protein sequence similarity, we identified those genes that were metabolism-related and specific to photosynthesis for further investigation. The selection of this group of genes was based on work of Liu et al (2007) and Lin et al (2008), who used a genomic PCR approach in their study of an albino mutant derived from tissue culture and determined that the albino mutant was the result of aberrations in the chloroplast DNA. Base on the protein sequence similarity, fourteen chloroplastencoded genes were identified in our cDNA library, including pyruvate dehydrogenase E1 component beta subunit (pdhB), NADH dehydrogenase subunit 5 (ndhF), photosystem I assembly protein (ycf3), DNA-directed RNA polymerase beta subunit (rpoC1), ribosomal protein S19 (rps19), ribosomal protein S3 (rps3), ribosomal protein L16 (rpl16), RNA polymerase beta subunit (rpoB), ribosomal protein S12 (rps12), ribosomal protein S11 (rps11), ATP synthase CF0 C chain (atpH), ATP synthase CF0 A chain (atpI), ribulose 1,5-bisphosphate carboxylase/oxygenase large subunit (rbcL), and photosystem II 43-kDa protein (psbC).…”
Section: Resultsmentioning
confidence: 99%
“…There are nearly 3000 chloroplast proteins synthesized in precursor form on cytosolic ribosomes and then targeted post-translationally to chloroplasts (Martin et al 1998). The chloroplast genome of the B. edulis albino mutant has been shown to be aberrated (Liu et al 2007;Lin et al 2008) and, consequently, the chloroplasts of the albino mutant were also abnormal. We therefore propose that the photosynthesis-related genes were down-regulated in the albino mutant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation